Pemanfaat Labu Siam (Sechium Edule) dalam Pembuatan Selai sebagai Alternatif Produk Olahan Lokal - Salmaa Lutfi Azhari; Alip Suroto; Salam Setiyawan (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Local food such as chayote (Sechium edule) has great potential as a healthy and environmentally friendly product that can support food security and improve the economic value of local communities. The innovation of processing chayote, particularly into jam, not only helps reduce agricultural waste but also opens up promising new market opportunities. This study applied an experimental design to produce chayote jam with variations in the use of granulated sugar, glucose, and the addition of mint leaves to enhance flavor. The production stages included grating fresh chayote, cooking until the water content was reduced, adding sugar and pectin to achieve a thick and stable texture, and finally packaging the product in sterilized glass jars. An organoleptic test was conducted with 32 panelists to evaluate the color, aroma, taste, texture, and overall acceptability of the product. The results indicated that jam dominated by granulated sugar (Sample A) gained the highest level of preference, with an overall acceptance of 81%. In contrast, jam made with full glucose substitution (Sample C) received the lowest score of 66%. Generally, chayote jam had a natural green color, distinctive aroma, and thick texture that were well accepted by consumers. The main factors determining jam quality were cooking techniques, the balance of thickening agents, and the proper combination of ingredients. Therefore, chayote jam has the potential to become an innovative, healthy, and value-added local food product. Support in the form of training, technology application, and promotional strategies is essential to strengthen its competitiveness, improve farmers’ welfare, and enhance food diversification based on Indonesia’s local resources.